2017
DOI: 10.1136/bjophthalmol-2016-310105
|View full text |Cite
|
Sign up to set email alerts
|

Fundus findings in a series of patients with extrapulmonary tuberculosis in Thailand

Abstract: Ocular lesions consistent with TB were not rare in a group of patients who were undergoing or had recently completed treatment for eTB. Fundus examination may provide diagnostic information that could influence a clinician's beliefs when diagnosing eTB. Given the low costs and immediate results of eye examination, this diagnostic test should be considered in patients suspected for eTB, especially when other tests are negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…In both series, choroiditis was the most common clinical presentation of OTB, and retinal vasculitis was rarely [28], or not seen [29]. The prevalence of OTB was slightly higher (~10%) when only patients with EPTB were analyzed [30]. Conversely, in patients with OTB, a recent multi-centric study found that 76.7% (604/787) did not have any past history of PTB/EPTB.…”
Section: Ocular Tb As a Form Of Extrapulmonary Tb: Host And Bacterial Factorsmentioning
confidence: 83%
“…In both series, choroiditis was the most common clinical presentation of OTB, and retinal vasculitis was rarely [28], or not seen [29]. The prevalence of OTB was slightly higher (~10%) when only patients with EPTB were analyzed [30]. Conversely, in patients with OTB, a recent multi-centric study found that 76.7% (604/787) did not have any past history of PTB/EPTB.…”
Section: Ocular Tb As a Form Of Extrapulmonary Tb: Host And Bacterial Factorsmentioning
confidence: 83%